FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM MENGAMBIL KEPUTUSAN BELANJA PADA AYU NADHI SUPERMARKET DENPASAR - Ida Ayu Trisna Wijayanthi (Forum Manajemen STIMI Handayani Denpasar, 2014)
Retail business in Indonesia is rampant not only in big cities but has penetrated intosmall cities and suburbs . This is due to a change in the behavior of people who are averse totraditional shopping outlets on the grounds of the limited time and less practical when shoppingin traditional markets . But for entrepreneurs who are engaged in retail businesses such assupermarkets , it is important to understand the consumer , consumer shopping behavior or socalledconsumerbehavior,anditisnotasmallmatterforeachmemberofaconsumersociety.AyuNadhiisafollowermarketinthefieldofsupermarketsitisimportanttoknow“whatarethefactorsthatconsumersconsiderinmakingdecisionsonthespendingNadiAyuSupermarket“.Fromthediscussionoftheresultsoftheanalysisofthefactorsthatconsumersconsiderinmakingdecisionson Ayu Nadi supermarket shopping , it can be concluded that there are 7 ( seven )factors that consumers consider in making decisions Supermarket shopping in Nadi Ayu namely :factor Teller Services , Room Cleanliness factor , factor freshness Products , Personal and Socialfactors , personal factors , factors security Guarantee and factor Locations